Flurbiprofen used in one-lung ventilation improves intraoperative regional cerebral oxygen saturation and reduces the incidence of postoperative delirium - Shen, Liang; Chen, Jia-qi; Yang, Xin-lu; Hu, Ji-cheng; Gao, Wei; Chai, Xiao-qing; Wang, Di (Frontiers in Psychiatry, 2022)
Background: We previously demonstrated that flurbiprofen increased arterial oxygen partial pressure and reduced intrapulmonary shunts. The present study aims to investigate whether flurbiprofen improves intraoperative regional cerebral oxygen saturation (rScO2) and reduces the incidence of postoperative delirium (POD) in elderly patients undergoing one-lung ventilation (OLV). Methods: One hundred and twenty patients undergoing thoracoscopic lobectomy were randomly assigned to the flurbiprofen-treated group (n=60) and the control-treated group (n=60). Flurbiprofen was intravenously administered 20 minutes before skin incision. The rScO2 and partial pressure of arterial oxygen (PaO2) were recorded during the surgery, and POD was measured by the Confusion Assessment Method (CAM) within five days after surgery. The study was registered in the Chinese Clinical Trial Registry with the number ChiCTR1800020032. Results: Compared with the control group, treatment with flurbiprofen significantly improved the mean value of intraoperative rScO2 as well as the PaO2 value (P < 0.05, both) and significantly reduced the baseline values of the rScO2 area under threshold (AUT) (P < 0.01) at 15 minutes, 30 minutes and 60 minutes after OLV in the flurbiprofen-treated group. After surgery, the POD incidence in the flurbiprofen-treated group was significantly decreased compared with that in the control group (P<0.05). Conclusion: Treatment with flurbiprofen may improve rScO2 and reduce the incidence of POD in elderly patients undergoing thoracoscopic one-lung ventilation surgery for lung cancer.